2022
DOI: 10.1002/pssa.202200503
|View full text |Cite
|
Sign up to set email alerts
|

Glass‐Assisted Chemical Vapor Deposition‐Grown Monolayer MoS2: Effective Control of Size Distribution via Surface Patterning

Abstract: Transition metal dichalcogenides (TMDs) are of interest for next‐generation electronics and optoelectronics owing to their unique optical and electronic functionalities. Although atomically thin flat TMD layers have been investigated in various device applications, pattern‐mediated growth serves great promise for revealing novel properties and application opportunities of TMDs. Herein, controlled size distribution of CVD‐grown monolayer MoS2 flakes by varying the distance between surface pattern features and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…Soda-lime glass lamellas, primarily composed of sodium ions as a catalyzer, were employed as promoters in this study to synthesize monolayer MoS 2 film, consistent with previous research [18,23,29,33]. The sodium concentration in the lamellas is critical in the molten glass-assisted process [31].…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Soda-lime glass lamellas, primarily composed of sodium ions as a catalyzer, were employed as promoters in this study to synthesize monolayer MoS 2 film, consistent with previous research [18,23,29,33]. The sodium concentration in the lamellas is critical in the molten glass-assisted process [31].…”
Section: Resultssupporting
confidence: 64%
“…In this study, to control carrier gas flow and eliminate system contamination, we constructed a homemade reactor with coaxial quartz tubes and a thermal holder, enabling the continuous growth of large-area MoS 2 films and flakes by employing a molten glass-assisted CVD process. In glass-assisted CVD growth approach, molten glass serves as a promoter, supplying a sodium source that facilitates the vaporization of MoO 3 , and reduces precursor contamination as compared to the conventional NaCl-assisted process, enhances the growth rate by reducing formation energy and establishes repeatable, straightforward routes for the growth of high-quality MoS 2 crystals [23,[29][30][31]. Subsequently, to investigate and enhance the optical properties of MoS 2 crystals, we treated the crystals with Li-TFSI salt.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Gokul et al achieved to grow large area monolayer MoS 2 through the modulation of the gas flow direction by placing barriers on the substrate and adjusting their geometry at the desired location [20]. In another study, we also investigated the flake size distribution depending on the distance between square patterns and observed that the flake size increased significantly with the spacing between the patterns [30]. On the basis of these studies, herein, the geometry-related nonlinear local gas flows induced by microchannel arrays with two different angular orientations to the incident flow, parallel and perpendicular, was observed to have affected the grain size distribution in terms of both the average position and the full-width-half-maximum.…”
Section: Resultsmentioning
confidence: 95%
“…These interactions include nonradiative recombination, charge transfer, and various excitonic transitions [7][8][9][10]. Moreover, the dielectric surroundings around 2D materials were reported to regulate the in-and out-coupling of light, resulting in significant variations in PL and Raman intensities [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%